2022
DOI: 10.3389/fvets.2022.842613
|View full text |Cite|
|
Sign up to set email alerts
|

Intraoperative Protective Mechanical Ventilation in Dogs: A Randomized Clinical Trial

Abstract: ObjectiveTo evaluate gas exchange, respiratory mechanics, and hemodynamic impact of mechanical ventilation with low tidal volume (VT) in dogs with the use of positive end-expiratory pressure (PEEP) or preceded by alveolar recruitment maneuver (ARM).Study DesignProspective randomized clinical trial.AnimalsTwenty-one healthy client-owned mesocephalic healthy dogs, 1–7 years old, weighing 10–20 kg, and body condition scores 4–6/9 admitted for periodontal treatment.MethodsIsoflurane-anesthetized dogs in dorsal rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…A low V T is used in humans because it has been proven that lung protective strategies reduce the risk of postoperative pulmonary complications [1]. In veterinary medicine, a recent study in healthy dogs, positioned in lateral recumbency and without an NMBA being used, evaluated the clinical feasibility of a V T of 8 mL/kg; the study concluded that this volume was sufficient to maintain normocapnia; however, this volume was not compared with other V T values [8]. The use of a low V T in dogs is still controversial, and there is evidence that volumes of 15 mL/kg are considered more appropriate to avoid hypercapnia [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…A low V T is used in humans because it has been proven that lung protective strategies reduce the risk of postoperative pulmonary complications [1]. In veterinary medicine, a recent study in healthy dogs, positioned in lateral recumbency and without an NMBA being used, evaluated the clinical feasibility of a V T of 8 mL/kg; the study concluded that this volume was sufficient to maintain normocapnia; however, this volume was not compared with other V T values [8]. The use of a low V T in dogs is still controversial, and there is evidence that volumes of 15 mL/kg are considered more appropriate to avoid hypercapnia [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Dogs come in a variety of breeds and have the largest variation in body size of all terrestrial vertebrates (34). Dogs have often been selected as surrogate models for humans in inhalation and lung function tests (35)(36)(37). A recent review of canine olfaction can be found in Kokocińska-Kusiak et al (38), which surveyed the physiological mechanisms and anatomical features that are implicated in the process of detecting and identifying odors.…”
Section: Dog (Canis Familiaris) Olfaction and Biomimetic Designmentioning
confidence: 99%